Training on MAXQDA for Qualitative Research Analysis to Empower Beginner Researchers in Academic Writing - Adi, Agung Nugroho; Azzuhri, Misbahuddin; Fithriana, Noora; Wibawanti, Krisetya Prili (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This community engagement program aimed to introduce beginner researchers to MAXQDA, a qualitative data analysis software, to enhance their understanding and application of qualitative research methods. The initiative sought to address the low interest in qualitative research by providing practical tools and training that simplify data interpretation and improve academic writing. Method: The program was conducted through face-to-face sessions, including theoretical instruction and hands-on practice. Participants learned to install and operate MAXQDA, analyze interview data, and visualize findings using features such as word clouds and code matrices. Practical Applications: The training enabled participants to conduct qualitative research more effectively, improving their ability to manage complex data and present results clearly. It also fostered greater interest in qualitative inquiry and encouraged the use of digital tools in academic research. Conclusion: MAXQDA proved to be a valuable tool for beginner researchers, enhancing their analytical skills and confidence in qualitative research. The program contributed to the development of methodological competence and improved the quality of academic writing.